The Calm before the Storm - AKBAS, FERHAT (Journal of Finance, 2016)
ABSTRACT I provide evidence that stocks experiencing unusually low trading volume over the week prior to earnings announcements have more unfavorable earnings surprises. This effect is more pronounced among stocks with higher short‐selling constraints. These findings support the view that unusually low trading volume signals negative information, since, under short‐selling constraints, informed agents with bad news stay by the sidelines. Changes in visibility or risk‐based explanations are insufficient to explain the results. This evidence provides insights into why unusually low trading volume predicts price declines.